Prenatal wildfire smoke PM2.5 exposure has carryover effects on the postnatal calf - Pace, Alexandra; Villamediana, Patricia; Rovai, Maristela; Ponce, Gabriella; Ellis, Natalie; Stegeman, Angela; Larson, Mallery; Konetchy, Denise E.; Rezamand, Pedram; Skibiel, Amy L. (Frontiers in Animal Science, 2025)
IntroductionHealth and performance of dairy calves can be influenced by the intra-uterine environment. Environmental stressors such as heat stress, maternal inflammatory status, and nutrient deficiencies have been shown to impair intra-uterine and postnatal development in dairy cattle, with implications for long-term productivity. Recent studies in primates have reported lower birth weights and altered infant inflammatory markers associated with maternal exposure to wildfire smoke particulate matter (wildfire-PM2.5) during pregnancy. However, the impact of intra-uterine exposure to wildfire-PM2.5 on dairy calf growth and health is unknown.MethodsHolstein heifer calves were born to cows exposed (WFS, n = 17) or unexposed (CON, n = 26) to wildfire smoke during mid gestation. Calves were monitored from birth through 6 months of life to evaluate growth patterns, health, and basal metabolic and inflammatory markers.ResultsAlthough there was no difference detected between groups in gestation length or calf frame size at birth, WFS calves had lower birth weights compared with that of CON (36.87 ± 0.87 kg vs. 40.82 ± 0.80 kg). WFS calves had greater average daily gain in the pre-weaning period but lower gain in the post-weaning period compared with CON. WFS calves also had greater plasma glucose concentrations in the pre-weaning period, lower β-hydroxybutyrate concentrations in the early post-weaning period, and greater non-esterified fatty acid concentrations for much of the pre-weaning and the early post-weaning period relative to those for CON calves. In addition, WFS calves had lower white blood cell counts throughout the preweaning period, coupled with greater serum albumin and lower serum amyloid A through the study, as well as lower haptoglobin concentrations at approximately 3 months of age. All calves received adequate passive transfer of immunity, but WFS calves had greater serum IgG concentrations, yet no difference was detected in apparent efficiency of IgG absorption compared with that for CON. WFS calves had lower odds of lung consolidation throughout the study.DiscussionOverall, these results indicate that prenatal exposure to wildfire particulates restricts fetal growth and programs postnatal calf metabolic and immune systems, which may have implications for future health and productivity.